2008
DOI: 10.1021/ja806262m
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir−Blodgett Assembly of Graphite Oxide Single Layers

Abstract: Single-layer graphite oxide can be viewed as an unconventional type of soft material and has recently been recognized as a promising material for composite and electronics applications. It is of both scientific curiosity and technical importance to know how these atomically thin sheets assemble. There are two fundamental geometries of interacting single layers: edge-to-edge and face-to-face. Such interactions were studied at the air-water interface by Langmuir-Blodgett assembly. Stable monolayers of graphite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
1,359
1
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,671 publications
(1,428 citation statements)
references
References 32 publications
45
1,359
1
6
Order By: Relevance
“…A typical broad peak near 10.21°(d-spacing B8.67 A) was observed for the GO powder. Compared with the parent GO, the peak of RGO Na-NH3 shows a obvious shift to higher 2y angles (25.04°; d-spacing B3.56 A) and is narrower than that of highly RGO (B23°; d-spacing B3.86 A) obtained previously 22 , suggesting that RGO Na-NH 3 was well ordered with two-dimensional sheets with more thorough removal of surface functional groups.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…A typical broad peak near 10.21°(d-spacing B8.67 A) was observed for the GO powder. Compared with the parent GO, the peak of RGO Na-NH3 shows a obvious shift to higher 2y angles (25.04°; d-spacing B3.56 A) and is narrower than that of highly RGO (B23°; d-spacing B3.86 A) obtained previously 22 , suggesting that RGO Na-NH 3 was well ordered with two-dimensional sheets with more thorough removal of surface functional groups.…”
Section: Resultsmentioning
confidence: 54%
“…GO was prepared from natural graphite powder (Bay Carbon; SP-1 graphite) using the modified Hummers method 22,41 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that amphiphilic GO sheets are able to be readily dispersed in aqueous solution and certain organic solvents, GO has now been considered as a popular precursor for fabricating large‐area graphene films 12, 13. Huang and co‐workers demonstrated that stable monolayer GO films could be achieved without using any stabilizing agent by the LB technique, as shown in Figure 1 14. The monolayers are easy to form a large‐area, and flat GO film with adjustable density from dilute close‐packed to overpacked monolayers.…”
Section: State‐of‐the‐art Self‐assembly Strategies Of Graphene Architmentioning
confidence: 99%
“…Scale bars in panels (a)–(d) represent 20 µm. Reproduced with permission 14. Copyright 2009, American Chemical Society.…”
Section: State‐of‐the‐art Self‐assembly Strategies Of Graphene Architmentioning
confidence: 99%